Association of cytokine genetic polymorphism with hepatites B infection evolution in adult patients - Cátia Silene Sversuti Ribeiro; Jeane Eliete Laguila Visentainer; Ricardo Alberto Moliterno (Memorias do Instituto Oswaldo Cruz, 2007)
The infection by the hepatitis B virus (HBV) has different forms of evolution, ranging from self-limited infection to chronic hepatic disease. The objective of this study was to evaluate the influence of cytokine genetic polymorphisms in the disease evolution. The patients were divided into two groups, one with chronic HBV (n = 30), and the other with self-limited infection (n = 41). The genotyping for TNF (-308), TGFB1 (+869, +915), IL-10 (1082, -819, and -592), IL-6 (-174), and IFNG (+874) was accomplished by the PCR-SSP (polymerase chain reaction with sequence specific primers technique using the One Lambda kit. Although no statistically significant differences were found between the groups, the combination of TNF -308GG and IFNG +874TA was found in a lower frequency in chronic patients than in individuals with self-limited infection (26.7 versus 46.3%; P = 0.079; OR = 0.40; IC95% = 0.14-1.11). In chronic patients with histological alterations it was not observed the genotype TGFB1+869 C/C, against 24.4% in the self limited infection group (100 versus 75.6%; P = 0.096; OR = 7.67; IC95% = 0.42-141.63). Further studies in other populations, and evaluation of a greater number of individuals could contribute for a better understanding of the cytokine genetic polymorphism influence in HBV infection evolution.